Life dynamism explorations on perceived quality of life and social exchange paradigms in casino settings - Chhabra, D.; Gursoy, D (Routledge, 2009)
This study explores quality of life (QOL) perceptions associated with casino gambling and examines the causes of variations in those perceptions using an integrated version of age-graded phenomenon and life characteristics. This study further examines the affects of gaming activity participation as a leisure activity on subsequent support for the casino gambling activity within the context of social exchange theory (SET). Data were collected from local residents residing within a 50-mile radius of existing casinos in a U.S. midwestern state. Results indicate similar gambling activity participation behavior across age groups. In addition, more subtle affects of age and life characteristics across age groups for the casino gambling activity are noted. Traces of similarities in perceptions, participation, and SET behavior are found to be more notable than absent.